PEMBINAAN LEMBAGA KEMASYARAKATAN DESA OLEH PEMERINTAHAN DAERAH KABUPATEN TUANTAN SINGINGI (STUDI KASUS LEMBAGA PEMBERDAYAAN MASYARAKAT DESA KOTO CERENTI KECAMATAN CERENTI TAHUN 2016) - Della Puspita; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Development of Village Community Institutions (LKD) aims to improve communitycapacity in institutions, increase community participation in rural development, empowercommunities in all aspects of life, improve the welfare of the community and realize qualityfamilies. The Community Empowerment Institute (LPM) is a partner institution of the Villageand Sub-District Governments in the aspects of planning, implementation and control ofcommunity-based development. The formulation of the problem in this research is how theVillage Community Institutional Development by Kuantan Singingi Regency Governmenttowards Community Empowerment Institution in Koto Cerenti Village and its obstacles.?The purpose of this research is to know the guidance by the Local Government ofKuantan Singingi Regency against Community Empowerment Institution in Koto CerentiVillage and the obstacles of Local Government of Kuantan Singingi Regency in fosteringCommunity Empowerment Institution of Koto Cerenti Village.The conclusion of this study is Based on the results of research that has been done onthe Development of Village Social Institutions By Local Government of Kuantan SingingiRegency (Case Study of Community Empowerment Institution in Koto Cerenti Village, CerentiSub-District, 2016), the researcher can conclude that the guidance done by the LocalGovernment towards the Institute of Empowerment Society has not been maximized. Obstaclesin: Lack of Budget For Development of LPM and Lack of Participation of LPM Members infollowing guidance given by Dinas Sosial Pemdayaan Masyarakat dan Desa.Keywords: Development of Village Community Institutions